2005
DOI: 10.1017/s1355617705051003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of attention and age on the occurrence of mirror movements

Abstract: This study utilised a finger force task to investigate the influence of attention and age on the occurrence of motor overflow in the form of mirror movements in neurologically intact adults. Forty right-handed participants were recruited from three age groups: 20-30 years, 40-50 years, and 60-70 years. Participants were required to maintain a target force using both their index and middle fingers, representing 50% of their maximum strength capacity for that hand. Attention was directed to a hand by activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 47 publications
9
51
0
Order By: Relevance
“…Many studies reported that MMs or unaffected motor cortex activation can be changed or manipulated by exercise [30,37,38,39,40,41,42,43,44]. This suggests that MMs can be manipulated by rehabilitative management.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that MMs or unaffected motor cortex activation can be changed or manipulated by exercise [30,37,38,39,40,41,42,43,44]. This suggests that MMs can be manipulated by rehabilitative management.…”
Section: Discussionmentioning
confidence: 99%
“…One could reasonably ask whether positive BOLD responses in the right sensorimotor cortex of the older adults might have accompanied motor overflows such as unintended mirror movements of their left hands (see Hoy, et al 2004). Motor overflow during maintained force generation tasks increases with aging and with fatigue (Baliz et al 2005;Addamo et al 2009). We looked for but did not see overt mirror movements of the left fingers or hands of any participants, either during training outside the scanner or during scans.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous "equalization" of left-right speed and reduction in mirror overflow movements may be due to callosal maturation involving the normal interplay between transcallosal facilitation and transcallosal inhibition. In healthy individuals, activation in one hemisphere during unilateral timed motor tasks facilitates activation of the same neural area in the opposite hemisphere via connections of the corpus callosum (Baliz et al, 2004;Ikeda, Luders, Burgess, & Shibasaki, 1992). Motor overflow occurs via this transcallosal facilitation early in life, until it becomes inhibited by (callosally mediated) interhemispheric inhibitory mechanisms arising from the contralateral hemisphere (Aranyi & Rosler, 2002;Baliz et al, 2004;Sohn, Jung, & Kaelin-Lang, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, activation in one hemisphere during unilateral timed motor tasks facilitates activation of the same neural area in the opposite hemisphere via connections of the corpus callosum (Baliz et al, 2004;Ikeda, Luders, Burgess, & Shibasaki, 1992). Motor overflow occurs via this transcallosal facilitation early in life, until it becomes inhibited by (callosally mediated) interhemispheric inhibitory mechanisms arising from the contralateral hemisphere (Aranyi & Rosler, 2002;Baliz et al, 2004;Sohn, Jung, & Kaelin-Lang, 2003). Transcallosal inhibition increases as the spread of cortical activation increases, which in turn allows for more efficient unilateral movement ).…”
Section: Discussionmentioning
confidence: 99%